A conjecture about the non-trivial zeroes of the Riemann zeta function - Alcántara Bode, Julio (Pontificia Universidad Católica del Perú, 2007)
Some heuristic arguments are given in support of the following conjecture: If the Riemann Hypothesis (RH) does not hold then the number of zeroes of the Riemann zeta function with real part σ >  ½ is infinite.
Keywords: Riemann Hypothesis; Non-Trivial Zeroes; Conjecture; https://purl.org/pe-repo/ocde/ford#1.01.00